SOCIAL NETWORK MARKETING, ATTITUDES TOWARD SOCIAL NETWORK MARKETING, AND CONSUMER ENGAGEMENT ON PURCHASE INTENTION OF BATIK COMPANY IN SURABAYA - Annas Syaifullah A.; Christina Rahardja Honantha (Perpustakaan Universitas Surabaya, 2019)
Abstract - This research aims to examine the effect of social network marketing, attitudes toward social network marketing, and consumer engagement to consumer purchase intention. This quantitative and causal type of research used questionnaires to obtain the data. Non-probability and purposive sampling method were used. 210 samples were taken whose are consumers of batik in Surabaya which an active users of social networking sites and know any sellers or brands of batik that perform a social network marketing and have ever commented on those social networking sites. The result analyzed by using SPSS 22.0 and AMOS 22.0. The result found that there is no direct effect between social network marketing and consumer purchase intention. However, consumer engagement fully mediates the relationship between social network marketing and consumer purchase intention. There is also an indirect effect from attitudes toward social network marketing between the relationship of social network marketing and consumer purchase intention. Keywords: Social Network Marketing, Consumer Engagement, Attitudes Toward Social Network Marketing, Consumer Purchase Intention